Diseño y desarrollo de vivienda de emergencia para catastrofes naturales Bogotá-Colombia (2014)
The design and development of emergency housing, aims to be the main tool for aid and assistance in overcoming the first phase of the disaster, caused by the disasters that have taken place in Colombia especially in the city of Bogotá from 2013. Every year, natural disasters in Colombia, affecting both rural and urban environments, where it looks broken, everyday life and daile development environments if communities, lack of prevention and few resources to deal with these situations, generate extensive damage to families and their habitat. The emergency action entities is rarely timely, the waiting time for first aid is long and the trauma of the affected communities increases when there is an action quickly. In this comes the need to establish mechanisms and guidelines to formulate solutions to such disasters standards and allow implantation , according to a selection of suitable land for temporary habitats arise according to the level of the disaster and by the number of people affected in a level 1 ( low catastrophe ) emergency housing and their respective service modules locate in metropolitan parks in a 2 level ( average catastrophe ) were implanted into lots strategic and level 3 ( high catastrophe ) were implemented in equipment with large air and easy accessibility.